2019
DOI: 10.1017/dmp.2019.81
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Medical Students Toward Volunteering in Emergency Situations

Abstract: Objective:With the rising incidence of health care emergencies, there has been a considerable burden placed on health care systems worldwide. We aimed to determine the willingness and capacity of medical students in Ireland to volunteer during health care emergencies.Methods:An online, cross-sectional survey of medical students at the National University of Ireland was conducted in 2015.Results:Respondents totaling 274 completed the survey (response rate – 30.1%). Of participants, 69.0% were willing to volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 13 publications
7
60
0
2
Order By: Relevance
“…Gouda and colleagues found that only a minority of students (4%) believed that they were prepared in terms of their current skills and experience. 28 These findings are recapitulated in other works that highlight that although the willingness to help persists, the lack of required knowledge and capability place these students, and patients, at risk in disaster situations. 30 31 Moreover, in Belgium, a study posits that students are not fully aware of the implications of providing care during a pandemic and, as such, are not suitably informed to make a decision.…”
Section: The Role Of Medical Students In a Crisismentioning
confidence: 52%
See 1 more Smart Citation
“…Gouda and colleagues found that only a minority of students (4%) believed that they were prepared in terms of their current skills and experience. 28 These findings are recapitulated in other works that highlight that although the willingness to help persists, the lack of required knowledge and capability place these students, and patients, at risk in disaster situations. 30 31 Moreover, in Belgium, a study posits that students are not fully aware of the implications of providing care during a pandemic and, as such, are not suitably informed to make a decision.…”
Section: The Role Of Medical Students In a Crisismentioning
confidence: 52%
“…Furthermore, of participants, 98% indicated altruism as a motivating factor for such volunteering. 28 Given the severity of COVID-19, however, is altruism alone sufficient to warrant the deployment of learners? While these motivations are commendable, they cannot be allowed to replace adequate clinical competencies.…”
Section: The Role Of Medical Students In a Crisismentioning
confidence: 99%
“…17,24,[34][35][36] One article reported over 59% of students willing to help, but only 23.7% of students believed they have the skills to help. 23…”
Section: Willingnessmentioning
confidence: 99%
“…Five studies measured students' skill levels; confidence to deal with emergency outbreaks ranged between 23.7 and 53.2% (Table 6). 23,26,[33][34][35] Three articles found that students' willingness was high, but when compared with their self-perceived knowledge, they did not feel prepared. [33][34][35] The perspective study by Starr describes "For me and my classmates, knowledge of the disease we were to face so soon was limited to the contents of that 1 lecture."…”
Section: Appropriatenessmentioning
confidence: 99%
“…This caused the passengers to get tired and return to their hometown, as well as other people to stop traveling. Voluntary program has positive impacts on volunteers themselves, including skills, social relations, and wellbeing [35][36][37] . However, it is also possible to determine whether other projects can be done at a lower cost.…”
Section: Discussionmentioning
confidence: 99%